(untitled) (Bioscience Journal, 2022)
Knowing the body parts affected in accidents at work is important to support managers and professionals in the sectors of work safety in the adoption of measures to promote health and prevent accidents. This study identifies the body parts affected in a work accident registered at the Reference Center for Occupational Health (CEREST) ​​in Sobral, Ceará, Brazil. It is a cross-sectional study, carried out from the database of the Reference Center for Occupational Health in Sobral, Ceará, Brazil. Data were collected between March 2015 and February 2016, from notifications of occupational accidents from the National System of Notifiable Diseases (SINAN), referring to the period from 2009 to 2013, totaling 2,438 occurrences. There was accidents involving the hands (37.6%), upper limbs (15.4%), lower limbs (13.0%) and feet (10.9%) were the most frequent. Were observed a greater number of victims of occupational accidents among men (90.7%) in the age group of 20 to 59 years (85.6%). There is, in fact, a predominance of body parts involved in occupational accidents in the population, with emphasis on the hand, upper limb, lower limb and foot (p = 0.0001). The study showed workers’ health promotion strategies should be encouraged in the workplace, as well as the guarantee of access and the correct use of personal protective equipment, for the prevention of risks, injuries and diseases, considering that accidents cause expenses for the State and losses for the victims.